2002
DOI: 10.1046/j.0306-5251.2001.01532.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a contraceptive patch (Evra/Ortho Evra) containing norelgestromin and ethinyloestradiol at four application sites

Abstract: Aims To determine the pharmacokinetic pro®le of norelgestromin (NGMN) and ethinyloestradiol (EE) following application of the contraceptive patch, Evra TM / Ortho Evra TM , at each of four anatomic sites (abdomen, buttock, arm, and torso). Methods Thirty-seven healthy, nonpregnant women aged 20±45 years participated in this open-label, four-period crossover study. Subjects were randomized to one of four treatment (site of application) sequences. Each patch was worn for 7 days, with a 1 month washout between tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 18 publications
(21 reference statements)
0
37
0
1
Order By: Relevance
“…These pharmacokinetic findings are similar to those reported in studies in which Ortho Evra™ was worn under "normal" conditions. [10][11][12][13] In the present study, there were no treatment effects (based on ANOVA) for NGMN. For EE, there was a statistically significant treatment effect (based on ANOVA) for AUC 0-240 h but not for C ss .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These pharmacokinetic findings are similar to those reported in studies in which Ortho Evra™ was worn under "normal" conditions. [10][11][12][13] In the present study, there were no treatment effects (based on ANOVA) for NGMN. For EE, there was a statistically significant treatment effect (based on ANOVA) for AUC 0-240 h but not for C ss .…”
Section: Discussionmentioning
confidence: 54%
“…Previous studies have reported the pharmacokinetic profile of NGMN and EE during 7 days of use [10][11][12] or over multiple cycles 13,14 of Ortho Evra™ wear. Evaluating a contraceptive patch under various conditions of heat and humidity is critical to ensure that pharmacokinetics and/or patch adhesion is not significantly altered in a manner that could reduce contraceptive protection.…”
mentioning
confidence: 99%
“…Women using this method may maintain their usual activities, including exercise, bathing, swimming, and use of a whirlpool or sauna. [2][3][4][5][6][7][8][9] The fact that Ortho Evra requires attention only once a week compared with the daily attention required with oral contraceptive pills (OCPs) has made this method appealing to adolescents. In studies in the adolescent age group, Ortho Evra provided excellent cycle control, and most adolescents were satisfied with the method.…”
Section: Introductionmentioning
confidence: 99%
“…Using typical pumping voltages of −0.6 V and 57 μA∕cm 2 , the power consumption of the CNT membrane is also highly favorable for compact devices. For a 25.8 cm 2 (commercially available size) nicotine transdermal patch made of a CNT membrane, a button cell battery with a capacity of 247 mWh can be pumping continuously for 12 d. Several patch products on the market are designed to wear 7 d at a time with acceptable levels of irritation (22).…”
Section: Resultsmentioning
confidence: 99%